2020
DOI: 10.1177/0734371x20967982
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing Motivation and Gender: Vignette-Based Study in a Local Government

Abstract: Public administration literature has been building more evidence about whistleblowing and gender, and whistleblowing and public service motivation. Yet, despite the well-developed theoretical argument of the socialization effect on public service motivation and gender, little effort has been undertaken to study their simultaneous relationships with whistleblowing. This study fills this gap suggesting that whistleblowing mechanisms for the public sector should allow no room for gender differences and should gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
(174 reference statements)
1
16
1
1
Order By: Relevance
“…Decades’ worth of research has highlighted the importance of whistleblowing for building democratic organizations (Brewer & Selden, 1998; Graham, 1986; Pemberton et al, 2012; Prysmakova & Evans, 2020; Taylor, 2018). Scholars view whistleblowing as a pro-social behavior or a form of protest, namely a positive organizational behavior, as whistleblowers wish to behave in a way that promotes public interest (De Maria, 2008).…”
Section: Background: Bureaucratic Whistleblowingmentioning
confidence: 99%
See 2 more Smart Citations
“…Decades’ worth of research has highlighted the importance of whistleblowing for building democratic organizations (Brewer & Selden, 1998; Graham, 1986; Pemberton et al, 2012; Prysmakova & Evans, 2020; Taylor, 2018). Scholars view whistleblowing as a pro-social behavior or a form of protest, namely a positive organizational behavior, as whistleblowers wish to behave in a way that promotes public interest (De Maria, 2008).…”
Section: Background: Bureaucratic Whistleblowingmentioning
confidence: 99%
“…In public administration, there has been a flurry of empirical research on whistleblowing, defining it as a prosocial or altruistic behavior, after the initial connection was made by Brewer and Selden (1998) (e.g., Caillier, 2015, 2017; Cho & Song, 2015; Potipiroon & Wongpreedee, 2021; Prysmakova & Evans, 2020). Together with Graham’s notion of principled dissent, which refers to “a protest and/or effort to change the organizational status quo because of a conscientious objection to current policy or practice” (Graham, 1986, p. 1), whistleblowing has received a fair amount of scholarly attention with belief that it would enhance bureaucratic effectiveness, accountability, and ethicality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putting these arguments into our study's context, research has also shown that women have higher moral awareness than men (Gammie and Gammie, 2009) and that women tend to make stricter ethical judgments than men (Nguyen et al, 2007). Yet, some studies, such as Prysmakova and Evans (2020), have failed to find a significant gender effect on ethical behavior. These mixed findings have led scholars such as Liyanarachchi and Adler (2011) to contend that the display of ethical behavior is situation specific.…”
Section: Gender As a Moderating Variablementioning
confidence: 78%
“…Although this approach has been used successfully in previous research in applied psychology (e.g., Cameron et al., 2016; Clinton & Pollini, 2021; Martínez-Íñigo et al., 2015), there is still a discrepancy between anticipating to feel something and actually experiencing it (Hassan & Wright, 2020). With that said, it is important to note that, in the PA literature, vignette experiments are widely used to predict attitudes and intentions (e.g., Prysmakova & Evans, 2022) and also the likelihood of engaging in behaviors (e.g., Christensen & Wright, 2018). Furthermore, several techniques were employed to enhance realism in the vignettes including the provision of baseline information to the participants.…”
Section: Discussionmentioning
confidence: 99%